Alcohol Consumption by Cirrhotic Subjects: Patterns of Use and Effects on Liver Function - Lucey, Michael R.; Connor, Jason T.; Boyer, Thomas D.; Henderson, J. Michael; Rikkers, Layton F. (The American journal of gastroenterology, 2008)
We investigated patterns of use of alcohol and its clinical effects among cirrhotic subjects who participated in a randomized clinical trial comparing the efficacy of transjugular intravenous portosystemic shunt and distal splenorenal shunt. There were 132 cirrhotic subjects, 78 with alcoholic liver disease (ALD), who were followed for a median of 49 months (range 2-93 months). Alcohol use was assessed by patient questionnaire, with corroboration by family members. Twenty-eight subjects (21%) were drinking at study entry and 60 subjects (45%) drank during follow-up. Heavy drinking (>4 drinks/day) was recorded in 25 ALD subjects, but in no non-ALD subjects (P < 0.0001). Drinking by ALD subjects was associated with a 153% increase in gamma-glutamyl transpeptidase (GGT) (P < 0.0001). The frequencies of death (46%vs 30%), ascites (33%vs 20%), encephalopathy (56%vs 42%), and variceal bleeding (11%vs 3%) were greater in the ALD group. In a Cox proportional hazards model only "ever heavy drinking" was associated with death (P= 0.0099), while recent heavy drinking increased the hazard of variceal hemorrhage dramatically (odds ratio 10.85). Whereas most cirrhotic subjects, alcoholic or not, did not drink during 5 yr of observation, heavy alcohol use occurred exclusively in ALD patients. Alcohol use by ALD subjects was associated with elevations in GGT and was linked to death and with rebleeding from shunt dysfunction.